A 1.5D fluid—Monte Carlo model of a hydrogen helicon plasma. (1st May 2022) - Agnello, R; Fubiani, G; Furno, I; Guittienne, Ph; Howling, A; Jacquier, R; Taccogna, F
Abstract: Helicon plasma sources operating with hydrogen or deuterium might be attractive for fusion applications due to their higher power efficiency compared to inductive radiofrequency plasma sources. In recent years, the resonant antenna ion device (RAID) has been investigating the physics of helicon plasmas and the possibility of employing them to produce negative ions for heating neutral beam injectors (HNBs). Herein, we present a fluid Monte Carlo (MC) model that describes plasma species transport in a typical helicon hydrogen plasma discharge. This work is motivated by an interest in better understanding the basic physics of helicon plasma devices operating in hydrogen and, in particular, the volume production of negative ions. This model is based on the synergy between two separate self-consistent approaches: a plasma fluid model that calculates ion transport and an MC model that determines the neutral and rovibrational density profiles of H 2 . By introducing the electron density and the temperature profiles measured by Langmuir probes as model constraints, the densities of ion species ( H +, H 2 +, H 3 +, H − ) are computed in a 1.5D (dimensional) geometry. The estimate of the negative ion density profile represents a useful benchmark that is comparable with dedicated diagnostics, such as cavity ring-down spectroscopy and Langmuir probe laser photodetachment. Neutral gas particles (atoms and molecules) are calculated assuming a fixed plasma background. This gas–plasma decoupling is necessary due to the different timescales of plasma (microseconds) and gas kinetics (milliseconds).